Change in Body Weight and Serum Albumin Levels in Febrile Neutropenic Lung Cancer Patients - Naomi Kayauchi; Yumi Nakagawa; Takako Oteki; Katsunori Kagohashi; Hiroaki Satoh (JMIR Publications, 2020)
Although advances have been made in the treatment and prevention of febrile neutropenia (FN) in cancer patients treated with chemotherapy, it is still a complication that requires clinical attention. Impaired nutritional status in patients who develop FN can affect the continuation of cancer treatment, but it has not been investigated. We conducted a retrospective longitudinal study in order to clarify (1) if body weight and serum albumin levels change in lung cancer patients who do and do not develop FN, and (2) if these indicators are more likely to worsen in patients with FN than in patients without FN. Patients undergoing cytotoxic chemotherapy between January 2011 and June 2020 were consecutively included in the study. Changes in body weight and serum albumin levels were investigated in a case-control study of patients with FN, and control patients without FN who were matched by age, gender, histopathology, and stage of lung cancer, at a ratio of 1:2. During the study period, 226 patients received cytotoxic chemotherapy. Among those, 33 (14.6%) patients developed FN during the first course of cytotoxic chemotherapy. We found a more pronounced decrease in both body weight and serum albumin level at four weeks after the initiation of chemotherapy in FN patients. In order to safely administer effective chemotherapy, medical staff need to pay close attention to the nutritional status of patients receiving chemotherapy.